Khūmư̄ samrap čhaonāthī patibatngān dān pā chumchon rư̄ang kānčhattham khō̜mūn bǣp mīsūanrūam phư̄a kānčhatkān pā chumchon yāng yangyư̄n (Samnak Čhatkān Pā Chumchon, Krom Pāmai, 2008)
Census study for forestry conservation and development in Thailand.